Metamorphosis of Topical Semisolid Products-Understanding the Role of Rheological Properties in Drug Permeation under the "in Use" Condition - Xuping Jin; Seyed Ebrahim Alavi; Abbas Shafiee; Vania Rodrigues Leite-Silva; Kiarash Khosrotehrani; Yousuf Mohammed (MDPI AG, 2023)
When developing topical semisolid products, it is crucial to consider the metamorphosis of the formulation under the "in use" condition. Numerous critical quality characteristics, including rheological properties, thermodynamic activity, particle size, globule size, and the rate/extent of drug release/permeation, can be altered during this process. This study aimed to use lidocaine as a model drug to establish a connection between the evaporation and change of rheological properties and the permeation of active pharmaceutical ingredients (APIs) in topical semisolid products under the "in use" condition. The evaporation rate of the lidocaine cream formulation was calculated by measuring the weight loss and heat flow of the sample using DSC/TGA. Changes in rheological properties due to metamorphosis were assessed and predicted using the Carreau-Yasuda model. The impact of solvent evaporation on a drug's permeability was studied by in vitro permeation testing (IVPT) using occluded and unconcluded cells. Overall, it was found that the viscosity and elastic modulus of prepared lidocaine cream gradually increased with the time of evaporation as a result of the aggregation of carbopol micelles and the crystallization of API after application. Compared to occluded cells, the permeability of lidocaine for formulation F1 (2.5% lidocaine) in unoccluded cells decreased by 32.4%. This was believed to be the result of increasing viscosity and crystallization of lidocaine instead of depletion of API from the applied dose, which was confirmed by formulation F2 with a higher content of API (5% lidocaine) showing a similar pattern, i.e., a 49.7% reduction of permeability after 4 h of study. To the best of our knowledge, this is the first study to simultaneously demonstrate the rheological change of a topical semisolid formulation during volatile solvent evaporation, resulting in a concurrent decrease in the permeability of API, which provides mathematical modelers with the necessary background to build complex models that incorporate evaporation, viscosity, and drug permeation in the simulation once at a time.